2015
DOI: 10.1039/c4ra12695e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic acetoxylation of lactic acid to 2-acetoxypropionic acid, en route to acrylic acid

Abstract: Catalytic acetoxylation of lactic acid to 2-acetoxypropionic acid, en route to acrylic acid Beerthuis, R.; Granollers, M.; Brown, D.R.; Salavagione, H.J.; Rothenberg, G.; Shiju, N.R. Published in: RSC Advances DOI:10.1039/c4ra12695eLink to publication Citation for published version (APA):Beerthuis, R., Granollers, M., Brown, D. R., Salavagione, H. J., Rothenberg, G., & Shiju, N. R. (2015). Catalytic acetoxylation of lactic acid to 2-acetoxypropionic acid, en route to acrylic acid. RSC Advances, 5(6), 4103-4108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
(64 reference statements)
0
22
0
Order By: Relevance
“…According to an extensive screening of the solid acid catalysts, Amberlyst 70, Nafion NR50, sulfonic acid‐functionalized activated carbon and sulfonated graphene were the most active solid replacements of sulfuric acid (with 83–90 % selectivity at 41–44 % LA conversion), while the activity of sulfated zirconia and zeolites was too low . The most promising procedure up to now is the use of a reactive distillation technology in presence of Amberlyst ion‐exchange resin as the solid catalyst, allowing to reach almost full LA conversion with up to 96 % APA selectivity…”
Section: Chemical Routes Of Acrylic Acidmentioning
confidence: 99%
“…According to an extensive screening of the solid acid catalysts, Amberlyst 70, Nafion NR50, sulfonic acid‐functionalized activated carbon and sulfonated graphene were the most active solid replacements of sulfuric acid (with 83–90 % selectivity at 41–44 % LA conversion), while the activity of sulfated zirconia and zeolites was too low . The most promising procedure up to now is the use of a reactive distillation technology in presence of Amberlyst ion‐exchange resin as the solid catalyst, allowing to reach almost full LA conversion with up to 96 % APA selectivity…”
Section: Chemical Routes Of Acrylic Acidmentioning
confidence: 99%
“…The dehydration reaction of lactic acid to acrylic acid is thoroughly studied in the gas phase in one step, but also in water under supercritical and subcritical conditions even indirectly (acetoxylation of lactic acid to 2 ‐acetoxypropionic acid that is then pyrolysed to acrylic acid) (Scheme ).…”
Section: Gas‐phase Dehydration Of Lactic Acid To Acrylic Acidmentioning
confidence: 99%
“…Recently, GO has been used as heterogeneous catalyst in reactions such as the oxidation of sulfides and thiols, oxidation of benzylic positions, and benzyl alcohol, ring opening of epoxides, aza-Michael addition reaction, synthesis of aldehydes or ketones and Friedel-Crafts addition of indoles to a,b-unsaturated ketones [8][9][10][11][12][13][14][15]. Moreover, sulfated GO was tested as a catalyst for the acetoxylation of lactic acid to 2-acetoxypropionic acid, the Beckmann condensation and hydration of propylene oxide [16,17]. In addition, some studies have demonstrated that the immobilization of transition metal nanoparticles on GO produce efficient catalysts [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%